Intercultural Communicative skills in the Multicultural Classroom for spanish as a Foreign Language - Diviñó González, Esther (Rastros Rostros, 2013)
This article reflects on the challenge created by the inappropriate use, on many occasions, of science, technology and communication, making it necessary to develop intercultural communication skills and shine a light on values in multicultural groups of students studying Spanish as a foreign language (e/el) outside their countries. The research in this article corresponds to the doctoral thesis Treatment of values in intercultural conditions based on reading comprehension: linguistic-didactic strategy . In this methodology, the author employed the action research model –germane to didactic disciplines– and ran a trial using a repertoire of texts taken from Cuban and Latin American literature, with the aim of working with these in advanced levels of e/el teaching. Based on the texts themselves, and the tasks taken from them, which included activities that referred to differences in cultures and values, it was confirmed that the majority of students gain intercultural skills when they better understand the values of “the other” and widen their appreciative horizons.